INTELLECTUAL CAPITAL RESEARCH TRENDS IN NON-PROFIT ORGANISATIONS: BIBLIOMETRIC ANALYSIS BASED ON SCOPUS DATA - Faiza , Nur Hidayatul; Hermawan , Sigit (Journal of Economic and Economic Policy, 2024)
This study explores the publication trends and impact of intellectual capital research within nonprofit organizations over the decade from 2014 to 2023. General Background: As the significance of intellectual capital in enhancing organizational performance becomes increasingly recognized, a deeper understanding of its application in nonprofit sectors is essential. Specific Background: Using bibliometric analysis, the research investigates 240 published articles from the Scopus database, focusing on the subjects of business management, economics, and social sciences. Knowledge Gap: While existing literature highlights the importance of intellectual capital, limited studies specifically address its implications in nonprofit contexts. Aims: The primary aim of this research is to identify trends, prominent authors, influential countries, and the overall landscape of intellectual capital publications in nonprofit organizations. Results: Findings indicate a significant increase in publications, with 87 articles published, predominantly by authors from the United States and Italy. Bontis emerged as the leading author with 115 citations in the Journal of Intellectual Capital. Novelty: This research employs VOSviewer software for bibliometric mapping, visualizing publication data and co-citation networks, thereby providing new insights into the research landscape. Implications: The outcomes of this study not only inform scholars about the trajectory of intellectual capital research in nonprofit organizations but also highlight potential areas for future inquiry, suggesting the need for exploration beyond the Scopus database to encompass broader perspectives from platforms like Web of Science and Google Scholar. This study ultimately contributes to the literature by underscoring the importance of intellectual capital in enhancing nonprofit organizational efficacy and encourages further investigation into this critical area.